Isolation and characterization of carcinogenic chromium reducing Pseudomonas aeruginosa from water of Buriganga river - Badhon, S.M. Saiful Islam (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2019.